2002
DOI: 10.1007/s00401-002-0528-6
|View full text |Cite
|
Sign up to set email alerts
|

Calpain activation in neurodegenerative diseases: confocal immunofluorescence study with antibodies specifically recognizing the active form of calpain 2

Abstract: The calcium-activated protease calpain cleaves a variety of biologically important proteins and serves, therefore, as a key regulator of many cellular functions. Activation of both main isoforms, calpain 1 and calpain 2, was demonstrated previously in Alzheimer's disease. In this report, antibodies specifically recognizing the active form of calpain 2 were used to investigate calpain 2 activation in a broad range of neurodegenerative diseases, utilizing multiple-label confocal immunofluorescence imaging. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 73 publications
5
59
0
Order By: Relevance
“…The results presented here are consistent with data suggesting that A␤ 1-42 induces a rise in resting Ca 2ϩ levels that is associated with an ER Ca 2ϩ leak ultimately leading to the pathological accumulation of Tau (81). Ca 2ϩ -activated proteases such as calpain have been related to Tau neurofibrillary pathology (82).…”
Section: Discussionsupporting
confidence: 91%
“…The results presented here are consistent with data suggesting that A␤ 1-42 induces a rise in resting Ca 2ϩ levels that is associated with an ER Ca 2ϩ leak ultimately leading to the pathological accumulation of Tau (81). Ca 2ϩ -activated proteases such as calpain have been related to Tau neurofibrillary pathology (82).…”
Section: Discussionsupporting
confidence: 91%
“…We found that in CGCs the activation of calpain mediated by NMDAR plays an important role in tau toxicity because its inhibition by calpeptin as well as by overexpression of its endogenous inhibitor calpastatin, significantly prevents neuronal death. Calpain is overactivated in AD brains (42,43) and in several tauopathies (44,45) in which it has been postulated to play an important role in development of cytoskeleton pathology by directly degrading or inducing the phosphorylation of its components. Among these, we have found that a fraction of tau is cleaved by calpain, with accumulation of a 17-kDa diagnostic fragment corresponding, as previously reported, to the tau region coded by tau- vector (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, conditions that prevented the generation of this fragment were accompanied by enhanced neuronal survival in central neurons (10,11). Because calpain is a calcium-dependent protease, its activity could be dysregulated in pathological conditions associated with abnormal calcium influx, as described in AD and many other tauopathies (12)(13)(14)(15)(16). Together, these data suggest that the calpain-mediated generation of this neurotoxic tau fragment might be part of the pathobiology of AD, and perhaps, all tauopathies.…”
Section: Introductionmentioning
confidence: 90%